Intracranial complications in adult patients with severe pneumococcal meningitis: a retrospective multicenter cohort study - Camille Legouy; Renaud Cornic; Keyvan Razazi; Damien Contou; Stéphane Legriel; Eve Garrigues; Pauline Buiche; Maxens Decavèle; Sarah Benghanem; Thomas Rambaud; Jérôme Aboab; Marina Esposito-Farèse; et al. (Annals of Intensive Care)
Abstract Background We aimed to investigate the association of intracranial complications diagnosed on neuroimaging with neurological outcomes of adults with severe pneumococcal meningitis. Methods We performed a retrospective multicenter study on consecutive adults diagnosed with pneumococcal meningitis requiring at least 48 h of stay in the intensive care unit (ICU) and undergoing neuroimaging, between 2005 and 2021. All neuroimaging were reanalyzed to look for intracranial complications which were categorized as (1) ischemic lesion, (2) intracranial hemorrhage (3) abscess/empyema, (4) ventriculitis, (5) cerebral venous thrombosis, (6) hydrocephalus, (7) diffuse cerebral oedema. The primary outcome was unfavorable outcome at 90 days after ICU admission, defined by a modified Rankin Scale (mRS) score > 2. Results Among the 237 patients included, intracranial complications were diagnosed in 68/220 patients (31%, 95%CI 0.25–0.37) who underwent neuroimaging at ICU admission and in 75/110 patients (68%, 95%CI 0.59–0.77) who underwent neuroimaging during ICU stay. At 90 days, 103 patients (44%, 95%CI 37–50) had unfavorable outcome, including 71 (30%) deaths. The most frequent intracranial complications were ischemic lesion (69/237 patients, 29%), diffuse cerebral oedema (43/237, 18%) and ventriculitis (36/237, 15%). Through multivariable analysis, we found that intracranial complications (adjusted odds ratio (aOR) 2.88, 95%CI 1.37–6.21) were associated with unfavorable outcome, along with chronic alcohol consumption (aOR 3.10, 95%CI 1.27–7.90), chronic vascular disease (aOR 4.41, 95%CI 1.58–13.63), focal neurological sign(s) (aOR 2.38, 95%CI 1.11–5.23), and cerebrospinal fluid leukocyte count < 1000 cell/microL (aOR 4.24, 95%CI 2.11–8.83). Competing risk analysis, with persistent disability (mRS score 3–5) as the primary risk and ICU-death as the competing risk, revealed that chronic alcohol consumption was the sole significant variable associated with persistent disability at 90 days (cause-specific hazard ratio 4.26, 95%CI 1.83–9.91), whereas the remaining variables were associated with mortality. Conclusions In adults with severe pneumococcal meninigitis, intracranial complications were independently associated with a higher risk of poor functional outcome, in the form of persistent disability or death. This study highlights the value of neuroimaging studies in this population, and provides relevant information for prognostication.